19th c. Coloured stuccos and plasters from Grilos' Church (Oporto, Portugal): Materials and techniques employed. Issue 3 (13th February 2016) - Salavessa, Eunice; Candeias, António; Mirão, José; Sousa, Luís M. O.; Duarte, Nelson; Jalali, Said; Salgueiro, Joana
Abstract: The Oporto's St. Lourenço Church of the Jesuit College is locally known, since the St. Augustin Barefooted Eremites occupation (1779/80), as Grilos' Church. The Oporto's siege laid by D. Pedro and D. Miguel (1832/33) succeed in the college abandonment by Grilo's Friars. Throughout Augustin Friars presence period, the white plasters of the nave (end of 18th c.) were executed and it was constructed the Holly Sacrament Chapel (early 19th c.) with neoclassic coloured stuccos and plasters, influenced by Robert Adam, Luigi Chiari and Teixeira Barreto ornamental motifs. Pigments were added to the external layer to imitate the marble and to achieve the "base" colour of the panels. This study of the blue, rose and white stuccos and plasters of H.S. Chapel of Grilo's Church allows carrying out useful database on the original mortars composition by the use of different analytical techniques, important to select the most adequate solutions for restoration interventions. Optical microscopy, XRD, TG‐DTA, SEM‐EDS, XRF analysis results were considered to identify the composition of different layers and to provide mineralogical, microstructure and chemical characterization of the mortars components and to quantify the binder content in those mortars. These results were compared with collected information on compositions from other sources. This study allowed the identification of the decay causes of decorative stuccos and plaster, suggesting that water retention in the masonries and wooden laths structure of the dome of the chapel is the main factor. © 2016 Wiley Periodicals, Inc. Col Res Appl, 41, 246–251, 2016